1983
DOI: 10.2134/agronj1983.00021962007500010035x
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluation of Selected Rhizobium in an Improved Legume Inoculant1

Abstract: Increased grain legume production depends on effective symbiotic dinitrogen fixation through successful legume inoculation. Inoculants containing high numbers ≥ l07/g of effective Rhizobium must withstand adverse field conditions. Field studies were performed to determine the effects of selected rhizobia in two different inoculant carriers on nodulation and performance of three grain legumes. The soil at the 1979 site (Vertic Haplaquept) contained = 103 cowpea Rhizobium and = 102 Rhizobium phaseoli per g of dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 17 publications
3
4
0
Order By: Relevance
“…This result clearly indicated that the native rhizobia effective in supplying N to host plants as the inoculated isolates did. In line with this result, Kremer and Peterson (1983) found that the N 2 fixation by peanut has been only increased when the inoculation improved the nodule weight.…”
Section: Discussionsupporting
confidence: 70%
“…This result clearly indicated that the native rhizobia effective in supplying N to host plants as the inoculated isolates did. In line with this result, Kremer and Peterson (1983) found that the N 2 fixation by peanut has been only increased when the inoculation improved the nodule weight.…”
Section: Discussionsupporting
confidence: 70%
“…However, correlations between the two groups were not high. Similar results were reported in cowpea (MILLER et al, 1986) and other legumes (KREMER & PETERSON, 1983;HEICHEL et al, 1981).…”
Section: And Discussionsupporting
confidence: 89%
“…As a result, inoculant rhizobia may only form 5-10% of the nodules produced in the first year, with the frequency with which they are found in nodules declining even further in subsequent crops. This has usually been perceived as a problem of competition between the inoculant rhizobia and those that are indigenous to the soil and has led to an intensive research effort emphasizing: (1) the selection of strains for competitive ability (Berg et ai., 1988;Caldwell, 1969;Johnson and Means, 1964;Klubek et al, 1988;Smith and Wollum, 1989), (2) the use oflarger than normal inoculation rates (Kapusta and Rouwenhoest, 1973;Weaver and Frederick, 1974a;, (3) development of improved inoculant carriers and delivery systems (Boonkerd et al, 1978;Kremer and Peterson, 1983;Stoddard, 1976;Wilson, 1975), (4) detailed ecological studies of the indigenous strains, and especially of those belonging to B. japonicum serogroup 123 Moawad et al, 1984;Sadowsky et al, 1987b;Viteri and Schmidt, 1987;, (5) studies on the molecular basis for competitive interaction, (6) repeated inoculation (Dunigan et al, 1984;Howieson, 1995;McLoughlin et al, 1990), and (7) host preference and restriction in nodulation (Cregan et al, 1986;Ferrey et al, 1994;Sadowsky et al, 1987b;Sadowsky et al, 1990;Sadowsky and Cregan, 1992). Strains of microorganisms which are stable members of the microbial community (members of the "local" microbial flora) appear to have a selective, competitive advantage in occupying available niches in that local environment (Atlas and Bartha 1993).…”
Section: Competition In Soil and Rhizospherementioning
confidence: 99%